Factors Influencing the Use and Choice of Formal Agriculture Credit Sources among Rice Farmers in Chitwan District, Nepal - Singh, Bikram Kumar; Singh, Om Prakash; Bhatta, Sushmita; Sapkota, Smriti; Mishra, Binayak Prakash (Agronomy Journal of Nepal, 2024)
Agriculture credit is important to sustain and further improve farming practices among rice farmers in developing countries like Nepal. Agriculture credit from formal sources safeguard farmers from fraud and misconduct which are common in informal sources. An investigation was carried out in Chitwan district of Nepal during January, 2023 to identify the factors influencing the use of formal agriculture credit among rice farmers. Further, factors influencing choice of sources among formal agriculture credit users was also assessed. Using random sampling, 59 formal agriculture credit users and 46 informal agriculture credit users were used for the study. Descriptive statistics and logit model were used to interpret the findings. Results revealed that use of formal agriculture credit increases with availability of off-farm income source and membership to agricultural cooperatives among farm household. Efforts should be made to promote participation in agricultural cooperatives to increase usage of formal agriculture credit among farm household. Similarly, choice of cooperatives over bank and microfinance increases with less formal education of the household head and non-availability of off-farm income source among farm household. Likely, choice of bank increases with no participation in agricultural cooperatives and choice of microfinance increases with higher contact with extension workers. Agriculture cooperatives should be further strengthened to provide timely and adequate credit, as it seems to support formal credit users characterized by lower formal education and no off-farm income source.